Subsídios à priorização de áreas com pouco conhecimento biológico para a conservação da biodiversidade na caatinga - Cavalcante, Carlos Victor Gonçalves (2023)
The main causes of the decline in Biological Diversity are intense changes in land use and natural landscapes. Based on satellite images, we analyzed geomorphological, physiographic, edaphic aspects and the level of anthropogenic disturbances of vegetation cover in an area classified by the Ministry of the Environment as a priority for biodiversity conservation in the state of Ceará. The study area is 3,923.41 km². Mapping was carried out by superimposing thematic maps of soils, elevation, geomorphology and landscape composition. From image analyzes on the level of conservation of vegetation cover, associated with a soil class map, we selected fragments of vegetation at similar altitudes and under different soil orders to verify the structure of shrub and tree vegetation. We identified three geomorphological units: Flattened Surfaces, Central Sertão Massifs and Sertanejo Patamar, with elevations ranging from 280 to 700 m. We mapped four soil classes: Planosols, Neossolos Litólicos Chernossolos and Luvissols. We identified two Phytoecological units, Submontane Deciduous Seasonal Forest (Matas Secas Serranas) with 27,110.00 thousand/ha, Estépica Savanna (Caatinga) 261,370.00 ha, followed by 53,640.00 ha of pasture, 33,830.00 ha of agricultural mosaic and pasture. Total beta diversity was β 0.89. The class of Chernosols and Litholic Neosols presented a beta diversity of β 0.76. The Chernosols presented greater richness, with 48 morphospecies, and a total of 2037 woody individuals, this is justified by their characteristics of depth and fertility, favoring the availability of nutrients. Our results indicate the need for purposeful territorial zoning, which can establish biodiversity conservation units, recover degraded areas and contain biodiversity loss. We thank CAPES for funding and the Phytogeography Laboratory.